2020
DOI: 10.1108/ijrdm-12-2019-0407
|View full text |Cite
|
Sign up to set email alerts
|

How sales promotion display affects customer shopping intentions in retails

Abstract: PurposeThe purpose of this paper is to examine the impact of sales promotion display on customer intentions to purchase and repurchase, focusing on the moderating roles of perceived product quality and price fairness.Design/methodology/approachThis study employs a descriptive, quantitative, non-experimental research method using a cross-sectional design with a self-administered questionnaire. In total, 415 department store customers responded to the survey through an online research panel provider in Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 64 publications
1
41
0
1
Order By: Relevance
“…If the promotional price is high, it makes consumers save more, making them more likely to buy goods or services (Tzeng et al, 2021). Previous research has also demonstrated the critical impact of customer buying decisions on sales promotion through discounts and cost reduction (Gorji and Siami, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…If the promotional price is high, it makes consumers save more, making them more likely to buy goods or services (Tzeng et al, 2021). Previous research has also demonstrated the critical impact of customer buying decisions on sales promotion through discounts and cost reduction (Gorji and Siami, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Researchers have investigated price reductions and their impact on consumers' decisions for a long time (Compeau and Grewal, 1998;Hardesty and Bearden, 2003;Mazumdar et al, 2005;Palazon and Delgado-Ballester, 2009). Even in the recent past, there has been plenty of research on how price promotions impact various aspects of consumer behaviour (Abdul, 2018;Gorji and Siami, 2020;Guha et al, 2018;Hardesty and Bearden, 2003;Jha et al, 2019;Kim and Lee, 2020;Mukherjee et al, 2017). While this stream of research has advanced our understanding of price promotions and consumer behaviour in general, little is known about the right timing to offer discounts during times of crisis.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Given the popularity of price discounts as a tactic to stimulate demand, there is a rich literature on the impact of price reductions on various aspects of consumer behaviour. This stream of literature has investigated the impact of price promotions on various aspects of consumer behaviour, such as shopping intentions (Gorji and Siami, 2020), evaluation of new products (Abdul, 2018; Jha et al. , 2019; Mukherjee et al.…”
Section: Consumers' Perceptions Of Price Reductions In Times Of Crisismentioning
confidence: 99%
“…Indeed, the higher the level of customer satisfaction, the greater is the repurchase intention (Gorji and Siami, 2020;Balaji et al, 2017). It can be argued, therefore, that customer service expectation is dependent on the customer's background because people in different cultures perceive services differently (Ladhari et al, 2011).…”
Section: Customer -Staff Interactionmentioning
confidence: 99%
“…The interaction between staff and customers can be decisive as regards generating customer satisfaction (Arora et al, 2020) and is influential in terms of customer service expectation. Indeed, the higher the level of customer satisfaction, the greater is the repurchase intention (Balaji et al, 2017;Gorji and Siami, 2020). It can be argued, therefore, that customer service expectation is dependent on the customer's background because people in different cultures perceive services differently (Ladhari et al, 2011).…”
Section: Customer-staff Interactionmentioning
confidence: 99%